Language Variation in The Speech of The “Napak Tilas” Community (NTPA) Mojoagung In Whatsapp Group - Ela Nur Fadhilah; Eva Eri Dia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This research aims to describe the types of language variations and language functions in the speech of the NTPA Mojoagung community in the WhatsApp group. The method in this research uses a qualitative descriptive approach. The data in this research are speech in the form of words and sentences containing dialectal, chronolectic, sociolectal language variations, and the function of instrumental, regulatory, representational, interactional, heuristic, personal language variations. The data source in this research is the Mojoagung Napak Tilas Pengembara (NTPA) community WhatsApp group. The data in this research is in the form of speech contained in the Mojoagung Napak Tilas Pengembara (NTPA) community WhatsApp group which contains language variations. Collecting data by means of documentation in the form of screen capture, data coding, and data identification. Data analysis used by researchers in this research is by describing the data, analyzing the data, and concluding the data. The results of this research show that there are three types of language variations in the speech of the Mojoagung Napak Tilas Pengembara (NTPA) community, namely dialect, chronolect and sociolect. (1) the dialects in the speech of the Mojoagung NTPA community are Palembang Malay dialect and Pontianak Malay dialect; (2) chronolect in the speech of the Mojoagung NTPA community, data in the form of vocabulary shortening, vocabulary reduction, and changes in language form; (3) sociolects found in the speech of the Mojoagung NTPA community consist of acrolects, basilecks, slang and vulgarity. Then six types of language function were found, namely instrumental, regulatory, representational, interactional, heuristic and personal. However, no imaginative language function was found in this study.